Astragali Radix-derived nitrogen-doped porous carbon: An efficient electrocatalyst for the oxygen reduction reaction. (11th January 2018) - Li, Jinmei; Wang, Wei; Wang, Fengxia; Kang, Yumao; Tan, Ting; Lei, Ziqiang
Abstract: The development of biomass-derived nitrogen-doped porous carbons (NPCs) for the oxygen reduction reaction (ORR) is important for sustainable energy systems. Herein, NPCs derived from Astragali Radix (AR) via a cost-effective strategy are reported for the first time. The as-prepared AR-950-5 catalyst shows a stacked layer-like structure and porosity. Notably, the optimized AR-950-5 delivers catalytic activity comparable to that of commercial Pt/C (C-Pt/C), with high onset potential, positive half-wave potential and large limiting current density. It also displays superior long-term stability and methanol tolerance for ORR. This work will pave the way for a new approach in the development of highly active and low-cost NPCs for fuel cells. Graphical abstract: Highlights: Novel biomass-derived NPCs are obtained from Astragali Radix. AR-950-5 possesses stacked layer-like structure and porosity. AR-950-5 exhibits superior ORR performance.